Development of chemogenetic methodology to investigate cortical mechanisms of cognition - Rotariu, SM (2019)
DREADDs (designer receptors exclusively activated by designer drugs) are virally mediated engineered muscarinic receptors that no longer bind their endogenous ligand acetylcholine but instead bind the clozapine metabolite, clozapine-N-oxide (CNO). These receptors are a very useful research tool for deconstructing behaviour due to their promoter-driven cell- specificity and potential spatial resolution, the low invasiveness associated with their use, reversibility and the temporal resolution of minutes to hours. This makes them ideal tools for linking cell-specific changes to behaviours that require longer testing duration such as learning and memory tasks.